Pengaruh Motivasi dan Keluarga Terhadap Minat Memilih Konsentrasi Pada Mahasiswa Fakultas Ekonomi Universitas Pendidikan Ganesha - Putra, Ida Bagus Komang Meka; Dharmayasa, I Putu Arya (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This study aims to analyze the influence of motivation and family on students' interest in choosing an academic concentration. The focus of this research is on students of the Faculty of Economics at Universitas Pendidikan Ganesha, class of 2021, who have selected their study concentration. The research method used is quantitative, employing multiple linear regression analysis techniques. The results indicate that motivation has a positive and significant influence on students' interest in choosing a concentration. Similarly, the role of the family also significantly affects students' academic decisions. Simultaneously, these two variables strongly influence students' interest in selecting a study path that aligns with their interests and career goals. These findings provide valuable insights for educational institutions to improve academic counseling strategies in helping students determine the most suitable concentration.